Hubungan Dukungan Keluarga Dengan Self Management Pada Pasien DM Tipe 2 - Nurhayati, Ceria; Veronika, Fira; Ambarsari, Ninik; Rustini, Sri Anik; Farida, Imroatul (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2022)
Introduction: Diabetes mellitus type 2 is a common problem that occurs i people who have metabolic disorders characterized by increased blood sugar duet o decreased secretion by pancreatic beta cells or impaired insulin function. The relationship of family support with people with type 2 DM is closely related to the existence of support, individuals will feel cared for considered to be in the support of their families. Objectives: The purpose of this study was to determine the relationship between family support and self management in type 2 diabetes mellitus in Sukodono Methods: The research design was analytic observational with cross sectional approach. The sampling technique uses Probability Sampling using simple random sampling. The population of Surabaya volunteers with a sample technique using simple random sampling obtained a sample of 109 respondents. Instrument used a questionnaire. Data were analyzed using the Spearman Rho test with a degree of significance Ïâ‰¤Â 0.05 Results: The results showed that most respondents had moderate family support. Most respondents had a good self managemente And obtained a relationship between family support and self management in Sukodono. From the statistical results of the Spearman rho test, it shows the value of r = 0.412 with a value of p = 0.05 Conclusions: The implication of this research is that high family support makes it easy for self management to lmanagement about their illnes.